2021
DOI: 10.1007/s00382-021-05857-y
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Tibetan Plateau on the North American summer monsoon precipitation

Abstract: It has been well known that the uplift of the Tibetan Plateau (TP) can significantly enhance the Asian monsoon. Here, by comparing the sensitivity experiments with vs without the TP, we find that TP uplift can also increase the precipitation of North American Summer Monsoon (NASM), with atmosphere teleconnection accounting for 6% and oceanic dynamical process accounting for another 6%. Physically, TP uplift generates a stationary Rossby wave train traveling from Asian continent to the North Atlantic region, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The CAM 5.1 is the atmospheric component of the Community Earth System Model version 1 (CESM1.0), developed by the National Center for Atmospheric Research (NCAR). It can simulate the atmospheric circulation in stand‐alone mode (e.g., Chen et al, 2022) or via coupling with land, ocean and sea‐ice model components (e.g., Wen et al, 2021). Detail on this model can be found in Neale et al (2010).…”
Section: Model Data and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CAM 5.1 is the atmospheric component of the Community Earth System Model version 1 (CESM1.0), developed by the National Center for Atmospheric Research (NCAR). It can simulate the atmospheric circulation in stand‐alone mode (e.g., Chen et al, 2022) or via coupling with land, ocean and sea‐ice model components (e.g., Wen et al, 2021). Detail on this model can be found in Neale et al (2010).…”
Section: Model Data and Methodsmentioning
confidence: 99%
“…Detail on this model can be found in Neale et al (2010). Previous studies reported that the NAM is well reproduced when using fine resolutions (e.g., 0.25 grid spacing) based on different models (Pascale et al, 2016(Pascale et al, , 2017Varuolo-Clarke et al, 2019), but some studies validated the good performance of the CESM with coarse resolution in simulating the atmospheric circulation and mean state of monsoon precipitation over North America (Bhattacharya et al, 2017;Wen et al, 2021). Given that we need to conduct a large number of sensitivity experiments, we set the resolution of CAM5.1 to be 1.9 × 2.5 horizontally with 30 vertical levels to minimize computing consumption.…”
Section: Model and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation